The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.4172/2167-7921.1000158
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Inflammatory Cytokines and Bone Metabolism Mediators in Patients Affected by Rheumatoid and Psoriatic Arthritis treated with Adalimumab

Abstract: Rheumatoid (RA) and Psoriatic arthritis (PsA) are characterized by extensive synovitis resulting in bone destruction in both diseases and new bone formation in PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Furthermore, treatment with anti-TNFα in PsA has demonstrated inhibition of radiographic progression and this seems to correlate to a reduction in circulating osteoclast precursors, indicating an osteoclast directed effect of TNFα [ 167 ]. Although most studies have found that the levels of TNFα and related cytokines are somewhat lower in PsA than those in RA, the role of TNFα in inflammation and joint destruction does not seem particularly different [ 168 , 169 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, treatment with anti-TNFα in PsA has demonstrated inhibition of radiographic progression and this seems to correlate to a reduction in circulating osteoclast precursors, indicating an osteoclast directed effect of TNFα [ 167 ]. Although most studies have found that the levels of TNFα and related cytokines are somewhat lower in PsA than those in RA, the role of TNFα in inflammation and joint destruction does not seem particularly different [ 168 , 169 ].…”
Section: Introductionmentioning
confidence: 99%